Epidemic preparedness and innovations in digital healthcare: enhancing post-pandemic speech-language pathology services for child and adolescent mental health in Qatar - Abdullah Amro; Hanan Abdallah Kotkot; Yahia Albobali; Prem Chandra; Yasser Saeed Khan (BMC, 2024)
Abstract Background This paper discusses the critical importance of epidemic preparedness and innovations in digital health care by examining the transformative impact on speech-language pathology (SLP) services in a specialist outpatient child and adolescent service (CAMHS). Method This retrospective review analyzes referral data from three periods: pre-pandemic (15 March 2019-14 March 2020), pandemic (15 March 2020-14 March 2021), and post-pandemic (15 March 2021-14 March 2022). Statistical analyses assess trends in referrals and diagnoses during these periods. Feedback was also obtained from Parents of children who received virtual consultations during the pandemic. Results The results reveal an increase in the demand for SLP services during and after the pandemic, with a surge in referrals (increased from 9.7 to 12.9% when compared pre-pandemic to post-pandemic periods; Chi-Square value 3.33, P = 0.068) for children with social communication challenges and autism spectrum disorder. Phone and video consultations were effectively adopted. Feedback from families shows a positive response (69%-98% of participants responded as strongly agreed and agreed on various items listed in feedback form specifically designed in line with the service objectives) to telehealth interventions, with many parents finding virtual consultations effective and helpful. Conclusions The study emphasizes the importance of telehealth SLP services in meeting the increasing demand for mental health interventions among children and adolescents. It suggests integrating telehealth into clinical practice beyond the pandemic and highlights the need for long-term evaluation and addressing potential barriers to access.